Screening of multidrug-resistant bacteria of antibiotic-associated diarrhea and their inhibition by leaf extracts of Moringa oleifera Lamk (Journal of Bio-Science, 2014)
Context: Emergence of multi drug resistance bacteria (MDRB) to human pathogenic infection is increasing day by day but the number of new drugs to overwhelm the problem is not sufficient. Evidences revealed that Moringa oleifera Lamk. has various pharmaceutical activities like antibacterial, antifungal, antispasmodic, anti-inflammatory, anticancer and diuretic. Herbal treatment may be one of the possible ways to treat diseases caused by multidrug-resistant bacteria. Objectives: The present research was undertaken to screen of multidrug resistant bacteria (MDRB) from antibiotic-associated diarrheal samples and to evaluate the potentiality of M. oleifera leaf extracts on these bacteria with the view to provide scientific evidence for its application in health remedy. Materials & Methods: Antibiotic-associated diarrheal fecal specimens were collected from pediatric ward of Rajshahi Medical College and cultured onto MacConkey agar. MDRB were determined by antibiotic susceptibility test, using disc-agar diffusion method. Biochemical tests of the MDRB were done according to Bergeys Manual of Determinative Bacteriology for identification of the species. Dried and fresh leaf of M. oleifera was used to prepare exaction with or without solvents such as hot water, cold water, chloroform, petroleum ether, acetone and ethanol, separately. Antibacterial assay was done by disc diffusion method and minimum inhibitory concentration of the extracts was also measured. Results: In the present study seven isolates were screened as MDRB and the highest prevalence (42.86%) was occurred in the age group of 25-36 months and the lowest (14.28) was in the group of